2019
DOI: 10.21926/obm.hg.1903029
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatitis in Solid Organ Transplant Patients: A Review of the Literature

Abstract: Acute pancreatitis is a highly morbid condition, which is widely recognized and well-defined in the general population. In this article, we summarized the current literature on acute pancreatitis in the setting of solid organ transplant, including patients who are listed for or have undergone transplantation. The incidence of acute pancreatitis in the solid organ transplant patient population ranges from 1-35%. Rates are lowest in cardiac and liver transplant patient populations and highest in the kidney and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 49 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…The immunosuppressive drugs including steroids, calcineurin inhibitors, mTOR inhibitors, and antiproliferative therapies like azathioprine are all risk factors for pancreatitis. Because renal transplant recipients are immunocompromised, they are more vulnerable to viral infections such as CMV, EBV, and varicella zoster, which can cause viral pancreatitis [ 23 ]. Other variables, such as hyperglycemia and hypertriglyceridemia, might cause pancreatitis in kidney transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…The immunosuppressive drugs including steroids, calcineurin inhibitors, mTOR inhibitors, and antiproliferative therapies like azathioprine are all risk factors for pancreatitis. Because renal transplant recipients are immunocompromised, they are more vulnerable to viral infections such as CMV, EBV, and varicella zoster, which can cause viral pancreatitis [ 23 ]. Other variables, such as hyperglycemia and hypertriglyceridemia, might cause pancreatitis in kidney transplant recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Acute pancreatitis can have a poor prognosis and can complicate the course of organ transplantation. It has been repeatedly documented in patients following kidney, bone marrow, intestine, heart, pancreas, and liver transplantations [ 4 , 13 ]. AP incidence and mortality in this group are often higher than in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…AP is a well-documented complication of organ transplantation, which occurs in up to 35% of transplant patients [ 4 ]. The incidence of AP following kidney transplantation is 1.2–7% and is associated with a high mortality rate [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The epidemiology of AP is well characterized in the general population, but more conflicting data are available for solid organ transplanted individuals. Graham D. et al, in a recent review, reported an incidence of 1-35%, with the highest rates in kidney and intestinal transplantation in pediatric populations ( 10 ).…”
Section: Introductionmentioning
confidence: 99%